Smart Operation of Electric Vehicles With Four-Quadrant Chargers Considering Uncertainties - Mehboob, Nafeesa; Restrepo, Mauricio; Canizares, Claudio A.; Rosenberg, Catherine; Kazerani, Mehrdad (Institute of Electrical and Electronics Engineers (IEEE), 2018)
Given the expected impact of electric vehicle (EV) charging on power grids, this paper presents a novel two-step approach for the smart operation of EVs with four-quadrant chargers in a primary distribution feeder, accounting for the uncertainties associated with EVs, and considering the perspectives of both the utility and the EV owners. In the first step of the proposed approach, the mean daily feeder peak demand and corresponding hourly feeder control schedules, such as taps and switched capacitor setpoints, considering the bidirectional active and reactive power transactions between EVs and the grid, are determined. A nonparametric bootstrap technique is used, in conjunction with a genetic algorithm-based optimization model, to account for EV uncertainties and discrete variables. In the second step, the maximum possible power that can be given to connected EVs at each node, while providing active and/or reactive power to maintain the peak demand value and corresponding feeder dispatch schedules defined in the first step, is computed every few minutes in a way which is fair to the EVs. The proposed approach is validated using the distribution feeder model of a real primary feeder in Ontario, Canada, considering significant EV penetration levels. The results show that the proposed approach could be implemented in practice to properly operate EVs, satisfying feeder, and peak demand constraints, which would be better than the business-as-usual practice or a popular heuristic method in terms of number of tap operations, system peak demand, and voltage regulation.
(© 2019 IEEE) Mehboob, N., Restrepo, M., Canizares, C. A., Rosenberg, C., & Kazerani, M. (2019). Smart operation of electric vehicles with four-quadrant chargers considering uncertainties. IEEE Transactions on Smart Grid, 10(3), 2999–3009. https://doi.org/10.1109/tsg.2018.2816404
Keywords: EV smart charging; bootstrap; distribution system management; electric vehicle; uncertainty; vehicle-to-grid